SOSIALISASI STRATEGI PEMANFAATAN REPLIKASI BASIS DATA (MASTER-MASTER DAN MASTER-SLAVE) UNTUK PENINGKATAN KINERJA APLIKASI DI RSIA MUTIARA BUNDA - Susilo, Herman; Fauzi, Dede; Ihksan, Muhammad; Abdillah, Nurul (Jurnal Abdimas Saintika, 2024)
The community service (Pengabmas) event held on February 3, 2024, at RSIA Bunda aimed to enhance application performance by implementing database replication strategies. The event focused on the theme "Socialization of Database Replication Strategies (Master-Master and Master-Slave) for Improving Application Performance at RSIA Mutiara Bunda." The activity began with an introduction to the fundamental concepts of database replication, presenting participants with the two main models: master-slave and master-master. The master-slave model, which involves one master server and several slave servers, and the master-master model, where each server functions as a master, were explained in detail. The discussion covered the advantages and disadvantages of each model in the context of enhancing application performance and system reliability. Participants, consisting of IT staff and information system managers at RSIA Mutiara Bunda, were provided with insights on selecting the appropriate replication model based on the specific needs of the hospital. Additionally, they received training on the techniques of implementing and managing database replication to ensure a more reliable and scalable system. The goal of this socialization was to enable RSIA Mutiara Bunda to apply suitable database replication strategies to optimize application performance and improve hospital operational efficiency. This community service not only enhanced the technical understanding of the participants but also contributed to the improvement of healthcare services through better information technology. Keywords : Community service, database replication, master-slave, master-master, application performance, RSIA Mutiara Bunda